Impact of nutrition counseling and physical activity on dietary intake, knowledge, and weight reduction among students with overweight and obese - Didit Damayanti; Fairuz Dhia Rabbani; Annisa Frida Rinjani; Gezza Anindhitha Kirana; Renata Claudia Agatha; Gurid Pramintarto Eko Mulyo (Healthcare in Low-resource Settings)
Overweight and obesity contribute to chronic diseases with an increasing prevalence in Jakarta. This study assessed the impact of combined nutritional counseling and physical activity interventions on body weight, energy, and nutrient intake among overweight and obese health students. A quasi-experimental study was conducted with 42 participants divided into three groups, each receiving different intervention combinations over one month. Body weight was measured using scales, food intake was assessed through 24-hour food recalls, and nutritional knowledge was evaluated using questionnaires. Statistical analysis was performed using paired t-tests, Wilcoxon test, or ANOVA tests in SPSS. Most participants were female (83.3%) and 19–29 years old (78.6%). After the intervention, significant reductions in body weight (p<0.001) were observed, along with improvements in nutritional knowledge (p<0.01) and physical activity levels (p<0.05) across all groups. Energy and macronutrient intake significantly decreased in Group I, whereas fiber intake increased in all groups (p<0.05). Combining nutritional counseling and weekly physical activity interventions effectively reduced body weight and improved dietary habits, nutritional knowledge, and physical activity. Implementing the "My Plate" guidelines along with increased physical activity is recommended as a practical strategy for obesity management among students. Universities should integrate these guidelines to promote healthy eating and maintain students' nutritional status.